Dissecting aneurysms of the distal segment of the posterior cerebral artery: clinical presentation and endovascular management. Issue 1 (December 2017) - Qian, Zenghui; Feng, Xin; Kang, Huibin; Wen, Xiaolong; Xu, Wenjuan; Li, Youxiang; Jiang, Chuhan; Wu, Zhongxue; Liu, Aihua
Abstract Backgroud We aimed to evaluate the clinical presentations and report the acceptable clinical and angiographic outcome of the distal posterior cerebral artery (PCA) dissecting aneurysms with parent artery occlusion (PAO). Methods From June 2006 to July 2013, 26 patients with PCA dissecting aneurysms were planned to be treated via endovascular PAO in our institution. Fourteen patients had ruptured aneurysms, and twelve patients had unruptured aneurysms. The endovascular modalities were the following: 1) PAO (n = 19), 2) palliative embolization (n = 5), and 3) proximal PAO (n = 2). Glasgow Outcome Scale (GOS) was used to assess the clinical outcome. Results The procedure was technically successful in all cases. In the PAO and proximal PAO group, all of the immediate angiography showed occlusion of the parent vessel, and follow-up imaging showed no recurrence of the aneurysms. In the palliative embolization group, one of five patients was died of rebleeding after the procedure, and follow-up digital subtraction angiography (DSA) showed the other four aneurysms recurred. Five procedure related complications occurred totally: rebleeding (n = 1), hemiparesis (n = 2), and hemianopsia (n = 2). Conclusion Dissecting aneurysms are dynamic lesions with variable and unpredictable evolution and a thorough treatment is warranted. Sacrificing the parent artery appears to be well tolerated for distal segment of PCA. We propose that this technique could be the first treatment option in treating dissecting aneurysms in this location. However, palliative occlusion of distal PCA dissecting aneurysms is not an advisable treatment option.